Method for promoting oxidation of sodium oxalate through coating of conductive polymer, composite sodium supplementing agent and application of composite sodium supplementing agent
By forming a conductive polymer coating on the surface of sodium oxalate particles, chemical oxidation polymerization reaction and trivalent iron ions are used to solve the problem that sodium oxalate is difficult to apply on a large scale due to high decomposition potential, and the effect of reducing decomposition potential and improving conductivity is achieved.
Patent Information
- Application Number
- CN202411978846.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
Sodium oxalate is difficult to apply on a large scale to sodium ion batteries due to its high decomposition potential.
By forming a conductive polymer coating on the surface of sodium oxalate particles, chemical oxidation polymerization reaction is used to introduce trivalent iron ions as oxidant to promote the oxidative decomposition of sodium oxalate.
It reduces the decomposition potential of sodium oxalate, improves its conductivity and stability, reduces the proportion of side reactions and inactive substances, and enhances its feasibility in large-scale applications.
Smart Images

Figure CN119786608A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion battery positive electrode sodium supplement, and relates to a method for promoting the oxidation of sodium oxalate by coating with a conductive polymer, a composite sodium supplement and application thereof. Background Art
[0002] In recent years, with the rapid development of electronic transportation, mobile devices and energy storage systems, rechargeable battery systems have received widespread attention. Due to the abundant reserves, wide distribution and low cost of sodium, sodium-ion batteries have become a promising alternative to lithium-ion batteries. However, in the early stages of the battery cycle, the hard carbon anode consumes the sodium source on the positive electrode side to form a solid electrolyte interface film. This irreversible sodium consumption significantly reduces the energy density of the battery and reduces its cycle stability, becoming one of the key issues that need to be urgently addressed in the development of sodium-ion battery technology.
[0003] Sodium supplementation refers to the pre-supplementation of active sodium in the positive or negative electrode, which can effectively compensate for the loss of active sodium during the initial cycle, and pre-form a solid electrolyte passivation layer to enhance the interface stability, improve the long-term cycle stability of the battery and increase the energy density. According to the different mechanisms, the sodium supplementation method can be divided into negative electrode pre-sodiumization and positive electrode sodium supplementation. Negative electrode pre-sodiumization can be divided into two main types: direct contact pre-sodiumization and solution chemical pre-sodiumization. The direct contact process involves simple mixing or contacting of sodium metal with the negative electrode. Driven by the potential difference, the active sodium ions from the sodium metal migrate to the negative electrode surface. Solution chemical pre-sodiumization uses a sodium-based organic reagent with strong reducing properties to transfer active sodium to the negative electrode material through redox reactions. However, the negative electrode pre-sodiumization method generally has problems such as residual metallic sodium or reagents on the surface, which limits its application. Positive electrode sodium supplementation includes the use of sodium-enriched positive electrode materials and positive electrode sodium supplementation agents. Sodium-enriched positive electrode materials are prepared by electrochemical or chemical methods to pre-store excess active sodium ions in the material. However, this method has a very limited sodium injection ratio and is only applicable to cathode materials with large vacancy crystal structures. The cathode sodium supplement undergoes electrochemical oxidation during the initial charge and discharge process, irreversibly releasing additional sodium ions to compensate for the loss of sodium. But it will inevitably decompose to produce gaseous or solid residual reactants, which will reduce the energy density of the battery.
[0004] Sodium oxalate is a green, air-stable, low-cost positive electrode sodium supplement consisting of a planar four-atom ring of oxalate ions and sodium ions. Sodium oxalate has a high theoretical capacity (400 mAh g-1), but its application is limited due to its high decomposition potential.
[0005] At present, the methods for reducing the decomposition potential of sodium oxalate mainly include mixing with a large amount of conductive carbon (such as the document Adv. Mater. 2020, 32, 2001419), introducing transition metal catalysts (such as the document ACS Appl. Mater. Interfaces 2024, 16, 15, 18971–18979), etc. These methods can reduce the decomposition potential of sodium oxalate to a certain extent, but there are problems such as serious side reactions, low proportion of active substances, and incomplete decomposition of sodium oxalate. Summary of the invention
[0006] The purpose of the present invention is to provide a method for promoting the oxidation of sodium oxalate by coating with a conductive polymer, a composite sodium supplement and its application, so as to solve the problem that sodium oxalate is difficult to apply on a large scale due to its high decomposition potential.
[0007] The purpose of the present invention can be achieved by the following technical solutions:
[0008] In a first aspect, the present invention provides a method for promoting oxidation of sodium oxalate by coating with a conductive polymer, comprising the following steps:
[0009] (1) dispersing sodium oxalate in a solvent to obtain a sodium oxalate dispersion, and then sequentially adding polyvinyl pyrrolidone and a conductive polymer monomer to obtain a first dispersion;
[0010] (2) dissolving an oxidant in another solvent to obtain a second dispersion;
[0011] (3) adding the second dispersion liquid dropwise to the first dispersion liquid, continuously stirring, filtering and drying to obtain a composite material powder as a composite sodium supplement.
[0012] Furthermore, in step (1), the mass ratio of sodium oxalate, polyvinyl pyrrolidone and conductive polymer monomer is 1000:(4-6):(50-100).
[0013] Furthermore, in step (1), the mass fraction of the sodium oxalate dispersion is 4 to 6%.
[0014] Furthermore, in step (1), the conductive polymer monomer is aniline, pyrrole or thiophene.
[0015] Furthermore, in steps (1) and (2), the solvent used is anhydrous ethanol or deionized water.
[0016] Furthermore, in step (2), the oxidant is a ferric salt or hydrogen peroxide. Specifically, the ferric salt is one or a combination of ferric chloride and ferric nitrate.
[0017] Furthermore, the added amounts of the second dispersion and the first dispersion satisfy that the molar ratio of the oxidant (eg, trivalent iron ions) to the conductive polymer monomer is 1:1-2.
[0018] Furthermore, the stirring is continued at a speed of 400 to 600 rpm, a temperature of 5 to 20° C., and a time of 6 to 24 hours.
[0019] Furthermore, the drying temperature is 70-90° C. and the drying time is 1-3 hours.
[0020] In a second aspect, the present invention provides a composite sodium supplement, which is prepared by the method as described above, and is obtained by forming a polymer conductive layer on the surface of sodium oxalate particles.
[0021] In a third aspect, the present invention provides an application of a composite sodium supplementer in sodium supplementation of a positive electrode of a sodium ion battery.
[0022] Conductive polymers are a class of organic polymer materials with electrical conductivity. They have similar electrical properties to inorganic semiconductors, but have lower production costs, lighter density, better processing performance and higher mechanical flexibility. Compared with traditional conductive carbon materials, the advantages of conductive polymers are their adjustable conductivity, excellent environmental stability and chemical functionality.
[0023] Chemical oxidative polymerization is an important method for preparing conductive polymers. It is low-cost, uses common and easily available oxidants and monomers, is simple to operate, does not require complex instruments and equipment, and is suitable for large-scale production. In this synthesis method, conditions such as monomer concentration, the nature of the oxidant, the ratio of oxidant to monomer, and polymerization temperature have a direct impact on the properties of the final conjugated conductive polymer, which provides flexibility for regulating the conductivity and structure of the polymer. Compared with other methods, such as electrochemical synthesis, the polymer powder obtained by chemical oxidative polymerization is more suitable for powder form applications, such as in batteries, sensors, and catalysts. Moreover, the reaction conditions of chemical oxidative polymerization are relatively mild and can be carried out at room temperature, which helps to protect the structure and properties of the polymer and avoid material degradation that may be caused by high temperature.
[0024] Based on the research of the above characteristics, the present invention takes polypyrrole coating and trivalent iron ion as an oxidant as an example. The trivalent iron ion can accept electrons, causing the conductive polymer monomer (taking pyrrole monomer as an example) to lose electrons and undergo oxidation reaction. In this process, the trivalent iron ion is reduced to divalent iron ion, and the pyrrole monomer is oxidized and forms a long chain structure of polypyrrole, and through continuous electron transfer reaction, a conjugated structure of polypyrrole is formed. In this process, the double bond of the pyrrole molecule is opened, and adjacent pyrrole units are connected by covalent bonds to form a linear or slightly branched polymer chain. In-situ polymerization allows a uniform polypyrrole layer to be directly formed on the surface of sodium oxalate particles. This polymerization reaction directly carried out on the substrate can ensure that there is a strong adhesion between the polymer layer and the substrate, thereby improving the uniformity and stability of the coating. During the reaction, conditions such as temperature, the ratio of oxidant to monomer, etc. can be accurately controlled to optimize the thickness, structure and conductivity of the polymer layer. The polypyrrole coating formed on the surface of sodium oxalate particles can not only improve its conductivity and reduce the decomposition potential, but also has a low proportion of inactive substances and few side reactions, thereby improving its feasibility in large-scale applications.
[0025] Compared with the prior art, the present invention has the following advantages:
[0026] (1) The conductive polymer coating layer can form a uniform film with high electronic conductivity, improve the charge transfer at the interface of sodium oxalate particles, and effectively promote the oxidative decomposition of sodium oxalate when only 5-10% inactive substances are introduced;
[0027] (2) The surface coating can provide a physical barrier to prevent side reactions and reduce electrode crack formation;
[0028] (3) The polymer chains of the polymer coating may entangle with each other, preventing direct contact between particles and thus reducing agglomeration. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 : is the charging curve of sample E1 obtained according to the conditions of Example 1.
[0030] Figure 2 This is the charging curve of sample E2 obtained according to the conditions of Example 2.
[0031] Figure 3 This is the charging curve of sample E3 obtained according to the conditions of Example 3.
[0032] Figure 4 This is the charging curve of sample E4 obtained according to the conditions of Example 4.
[0033] Figure 5 This is the charging curve of sample E5 obtained according to the conditions of Example 5.
[0034] Figure 6 This is the charging curve of sample E6 obtained according to the conditions of Example 6.
[0035] Figure 7 This is the charging curve of sample E7 obtained according to the conditions of Example 7.
[0036] Figure 8 This is the charging curve of sample E8 obtained according to the conditions of Example 8.
[0037] Fig. 9 This is the charging curve of sample E9 obtained according to the conditions of Example 9.
[0038] Fig.10 This is the charging curve of sample C1 obtained under the conditions of Comparative Example 1.
[0039] Fig.11 This is the SEM image of sample E4 obtained according to the conditions of Example 4. DETAILED DESCRIPTION
[0040] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0041] In order to form a thin and uniform polymer conductive layer on the surface of sodium oxalate particles to solve the problem that sodium oxalate is difficult to apply on a large scale due to its high decomposition potential, the present invention provides a method for promoting the oxidation of sodium oxalate by coating with a conductive polymer, comprising the following steps:
[0042] (1) dispersing sodium oxalate in anhydrous ethanol to obtain a sodium oxalate dispersion, and then sequentially adding polyvinyl pyrrolidone and a conductive polymer monomer to obtain a first dispersion;
[0043] (2) dissolving a trivalent iron salt in anhydrous ethanol to obtain a second dispersion;
[0044] (3) The second dispersion liquid is added dropwise to the first dispersion liquid, and the mixture is continuously stirred for reaction, filtered and dried (the drying temperature is selected to be about 80° C.) to obtain a composite material powder as a composite sodium supplement.
[0045] Based on the above method, the present invention provides the following Examples 1-9 and Comparative Example 1.
[0046] In the following examples, unless otherwise specified, raw materials or processing techniques are conventional commercially available raw materials or conventional processing techniques in the art.
[0047] Embodiment 1:
[0048] 30 μL of pyrrole monomer was added to an ethanol dispersion containing 0.5 g of sodium oxalate, the molar ratio of ferric chloride to polymer monomer was 1:1, the reaction temperature was 20°C, the reaction time was 12 h, and the composite sodium supplement sample E1 was obtained.
[0049] Embodiment 2:
[0050] 30 μL of pyrrole monomer was added to an ethanol dispersion containing 0.5 g of sodium oxalate, the molar ratio of ferric chloride to polymer monomer was 1:2, the reaction temperature was 20°C, the reaction time was 12 h, and the composite sodium supplement sample E2 was obtained.
[0051] Embodiment 3:
[0052] 30 μL of pyrrole monomer was added to an ethanol dispersion containing 0.5 g of sodium oxalate, the molar ratio of ferric chloride to polymer monomer was 1:1, the reaction temperature was 5°C, the reaction time was 6 h, and the composite sodium supplement sample E3 was obtained.
[0053] Embodiment 4:
[0054] 30 μL of pyrrole monomer was added to an ethanol dispersion containing 0.5 g of sodium oxalate, the molar ratio of ferric chloride to polymer monomer was 1:1, the reaction temperature was 5°C, the reaction time was 12 h, and the composite sodium supplement sample E4 was obtained.
[0055] Embodiment 5:
[0056] 30 μL of pyrrole monomer was added to an ethanol dispersion containing 0.5 g of sodium oxalate, the molar ratio of ferric chloride to polymer monomer was 1:1, the reaction temperature was 5°C, the reaction time was 24 h, and the composite sodium supplement sample E5 was obtained.
[0057] Embodiment 6:
[0058] 30 μL of aniline monomer was added to an ethanol dispersion containing 0.5 g of sodium oxalate, the molar ratio of ferric chloride to polymer monomer was 1:1, the reaction temperature was 20°C, the reaction time was 12 h, and the composite sodium supplement sample E6 was obtained.
[0059] Embodiment 7:
[0060] 30 μL of thiophene monomer was added to an ethanol dispersion containing 0.5 g of sodium oxalate, the molar ratio of ferric chloride to polymer monomer was 1:1, the reaction temperature was 20°C, the reaction time was 12 h, and the composite sodium supplement sample E7 was obtained.
[0061] Embodiment 8:
[0062] 30 μL of pyrrole monomer was added to a deionized water dispersion containing 0.5 g of sodium oxalate, the molar ratio of ferric chloride to polymer monomer was 1:1, the reaction temperature was 20°C, the reaction time was 12 h, and the composite sodium supplement sample E8 was obtained.
[0063] Embodiment 9:
[0064] 30 μL of pyrrole monomer was added to an ethanol dispersion containing 0.5 g of sodium oxalate, the molar ratio of hydrogen peroxide to polymer monomer was 1:1, the reaction temperature was 20°C, the reaction time was 12 h, and the composite sodium supplement sample E9 was obtained.
[0065] Comparative Example 1:
[0066] The uncoated sodium oxalate was directly used as the sodium supplement sample C1.
[0067] Depend on Figure 1-10 The charging curve shows that the sodium oxalate composite sodium supplement electrode prepared under the reaction conditions of Example 4 has the best performance, with an initial decomposition potential lower than 4.05V, an average oxidation potential of about 4.1V, and a mass specific capacity of more than 99% of the theoretical value. Compared with the average oxidation potential of more than 4.55V and a specific capacity of only about 35% of the sodium oxalate sample without coating treatment in Comparative Example 1, it is found that all coating methods can reduce the decomposition potential of sodium oxalate and improve the capacity utilization rate to a certain extent.
[0068] Depend on Fig.11 The SEM results show that the sodium oxalate composite sodium supplement prepared under the reaction conditions of Example 4 has a uniform particle size of about 100 nm, and a relatively uniform conductive polymer coating layer can be observed on its surface, which helps to improve the reaction kinetics.
[0069] The composite sodium supplement samples of Examples 1-9 and Comparative Example 1 were used to prepare positive electrode sheets and button batteries in the following manner:
[0070] (1) A slurry was prepared with a ratio of composite sodium supplement sample: Ketjen black (conductive carbon): polyvinylidene fluoride = 80:10:10, and the slurry was coated on an aluminum foil with a thickness of 75 μm;
[0071] (2) placing the positive electrode sheet obtained in (1) in an oven at 80°C for 12 hours;
[0072] (3) The dried positive electrode was cut into discs with a diameter of 12 mm, and metallic sodium was used as the counter electrode and glass fiber separator, 1M NaClO4 in DEC:EC=1:1Vol%with 5%FEC was used as the electrolyte, and a 2032 type button battery was equipped. It was charged at a constant current rate of 0.1C to 4.5V, and then charged at a constant voltage of 4.5V to 0.02C (current cutoff).
[0073] The contents of the electrochemical test include:
[0074] Instrument: Xinwei battery tester
[0075] Method: Constant current and constant voltage charging
[0076] (1) First cycle charging capacity:
[0077] The amount of charge that a battery can hold per unit mass or volume of active material during the first charge, usually expressed in milliampere-hours per gram (mAh / g) or milliampere-hours per cubic centimeter (mAh / cm 3 )express.
[0078] (2) Average oxidation potential:
[0079] The voltage value when the battery's charge capacity reaches half of the theoretical capacity of sodium oxalate during the first charging process.
[0080] Table 1 The first cycle charge specific capacity and average oxidation potential of the above examples
[0081]
[0082]
[0083] As can be seen from Table 1, the oxidation potential of polypyrrole-coated sodium oxalate is lower than that of polyaniline-coated samples. Both polypyrrole and polyaniline molecular chains have conjugated structures, that is, there are alternating single and double bonds in the molecular chain, which makes the π electrons delocalized throughout the main chain or conjugated chain segment. This delocalized π electron system provides molecular orbitals for charge carriers, thereby allowing charge transfer. The conjugation length and conjugated chain structure of polypyrrole may be more conducive to the delocalization and transfer of electrons than polyaniline, which may be one of the reasons why the polypyrrole-coated samples have better conductivity.
[0084] At the same time, when the type of oxidant is changed from ferric chloride to hydrogen peroxide, the average oxidation potential of the sodium oxalate electrode increases significantly. In ethanol solution, the redox potential of ferric chloride is higher, which enables it to more effectively capture electrons, thereby promoting the oxidative polymerization of pyrrole monomers. In contrast, hydrogen peroxide has strong oxidizing properties under acidic conditions, but its oxidizing properties may be inhibited in a non-acidic environment such as ethanol. In addition, the hydroxyl radicals produced by the decomposition of hydrogen peroxide may react more easily with ethanol rather than with pyrrole monomers, which will reduce the polymerization efficiency.
[0085] Table 1 also shows that when the ratio of oxidant to polymer monomer is 1:1, the performance of the composite sodium supplement is better. Since the polymerization reaction is a chain reaction process, including three steps: chain initiation, chain growth and chain termination, the molar ratio of monomer to oxidant will affect the progress of these steps. In the chain initiation stage, the oxidant acts as an initiator, and its concentration determines the rate of free radical generation. If the molar ratio of oxidant to monomer is not appropriate, it may lead to low initiation efficiency and affect the polymerization rate. In the chain growth stage, the molar ratio of monomer to oxidant affects the conversion rate of monomer and the length of polymer chain. A suitable molar ratio can promote the effective conversion of monomers, while an improper ratio may lead to premature termination or excessive growth of polymer chains. In the chain termination stage, if the oxidant is excessive, it may react with chain free radicals to cause chain termination, thereby reducing the molecular weight of the polymer and affecting its performance.
[0086] In addition, the present invention found that as the reaction time increases, the oxidation potential of the composite sodium supplement first decreases and then increases slightly. The length of the polymerization time directly affects the degree of polymerization and molecular weight distribution of the polymer. A shorter reaction time may result in insufficient degree of polymerization and a shorter polymer chain; if the polymerization time is too long, the molecular weight may be too large, affecting the processing properties of the polymer, and the molecular weight distribution may also become uneven.
[0087] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for promoting the oxidation of sodium oxalate by coating with a conductive polymer, characterized in that: The following steps are involved: (1) dispersing sodium oxalate in a solvent to obtain a sodium oxalate dispersion, and then sequentially adding polyvinyl pyrrolidone and a conductive polymer monomer to obtain a first dispersion; (2) dissolving an oxidant in another solvent to obtain a second dispersion; (3) adding the second dispersion liquid dropwise to the first dispersion liquid, continuously stirring, filtering and drying to obtain a composite material powder as a composite sodium supplement.
2. The method for promoting oxidation of sodium oxalate by coating with a conductive polymer according to claim 1, characterized in that: In step (1), the mass ratio of sodium oxalate, polyvinyl pyrrolidone and conductive polymer monomer is 1000:(4-6):(50-100).
3. The method for promoting oxidation of sodium oxalate by coating with a conductive polymer according to claim 1, characterized in that: In step (1), the mass fraction of the sodium oxalate dispersion is 4-6%.
4. The method for promoting oxidation of sodium oxalate by coating with a conductive polymer according to claim 1, characterized in that: In step (1), the conductive polymer monomer is aniline, pyrrole or thiophene.
5. The method for promoting oxidation of sodium oxalate by coating with a conductive polymer according to claim 1, characterized in that: The oxidant is a trivalent iron salt or hydrogen peroxide.
6. The method for promoting oxidation of sodium oxalate by coating with a conductive polymer according to claim 5, characterized in that: The ferric iron salt is one of ferric chloride and ferric nitrate or a combination of both.
7. The method for promoting oxidation of sodium oxalate by coating with a conductive polymer according to claim 1, characterized in that: The added amounts of the second dispersion and the first dispersion satisfy that the molar ratio of the oxidant to the conductive polymer monomer is 1:1-2.
8. The method for promoting oxidation of sodium oxalate by coating with a conductive polymer according to claim 1, characterized in that: The continuous stirring speed is 400-600 rpm, the temperature is 5-20°C, and the time is 6-24 hours.
9. A composite sodium supplement, prepared by the method according to any one of claims 1 to 8, characterized in that: The method is obtained by forming a polymer conductive layer on the surface of sodium oxalate particles.
10. Use of the composite sodium supplement agent according to claim 9 in sodium supplementation of the positive electrode of a sodium ion battery.
Citation Information
Patent Citations
Sodium ion composite positive electrode material and preparation method and application thereof
CN115642237A
Hard carbon material externally coated with soft carbon and sodium supplement as well as preparation method and application of hard carbon material
CN117334901A
Positive electrode lithium supplement agent and preparation method thereof, positive electrode and lithium ion battery
CN118231801A
Sodium supplementing material and preparation method thereof, positive pole piece and sodium ion battery
CN118867247A
Pre-sodium-modified current collector and preparation method and application thereof
CN118867259A